Exploring staff and service user experiences of personality disorder services in open prisons: A qualitative study of Pathways Enhanced Resettlement Support - Georgina Mathlin; Hannah Jones; Carine Lewis; Claudia Cooper; Mark Freestone (PLoS ONE, 2026)
Re-entering the community following a prison sentence is a critical period for rehabilitation, especially for people in prison with a likely diagnosis of personality disorder. A joint health and criminal justice initiative across England and Wales, called the Offender Personality Disorder (OPD) Pathway, aims to support individuals with a likely diagnosis of personality disorder with services across different prison and community settings. Pathways Enhanced Resettlement Services (PERS) are OPD services operating in five open prisons in England, which aim to support people at high risk of being returned to closed conditions or reoffending in the community after release. We aimed to understand how service users and staff experience PERS. We purposively selected staff and service users within male prisons to encompass a range of staff roles and current and ex-service users. We conducted semi-structured interviews with ten staff and nine service users (seven current and two ex-service users). We conducted a reflexive thematic analysis, generating three themes: (1) “A shock to the system”: this theme describes the challenges of adapting to open prison culture as a liminal space between closed conditions and the community; and understanding and accepting PERS as a service to provide support within and beyond that space. (2) “We’ve got some understanding of their journey”: This theme describes how service users felt valued by PERS support that was centred around their needs, a personalised approach that enabled the development of trusting, therapeutic relationships. (3) “Internal states can be real barriers to progression”: this theme describes how PERS staff were able to use the therapeutic relationships they developed with service users to support them to progress through their sentence. Staff and service users felt that PERS provided support to progress through open prison, largely by developing positive trusting relationships and individualised support plans.